Answer:
y = (x^2 + 6) / 2
Step-by-step explanation:
Original function:
To find the inverse of a function we have to switch the x and y values and solve for y again
x = sqrt (2y-6)
To get rid of a square root we square the square root so:
x^2 = 2y-6
Add 6
x^2 + 6 = 2y
Divide by 2
y = (x^2 + 6) / 2
Answer:
See explanation below
Step-by-step explanation:
The best explanation is noticing that in order to get from the point R (12, 1) to the point Q (7, 4) we move 5 units to the left and 3 units up. And to go from point Q (7, 4) to point P (2, 7) we do exactly the same: move 5 units to the left and 3 units up. That means that these points are all connected via the same rate of change: - 3/5, which is in fact the slope of the line the three points belong to.
<span>Answer:
MgF2 ====⇒ Mg+2 + 2F-
Ksp = [Mg+2][F-]^2
Let S = molar solubility of MgF2
[Mg+2] = S ; [F-] = 2s
Since the [F-] is initially 0.40 M, then [F-] = 0.40 + 2S
6.4 x 10^-9 = (S) (0.40 + 2S)^2 ; one can neglect the 2S in the 0.40 + 2S expression since it is very, very small compared to the 0.40 already present.
6.4 x 10^-9 = S(0.40)^2
S = 4.0 x 10^-8
Molar solubility = 4.0 x 10^-8</span>
Is there a picture to go with it